The Impact of Demand and Price Expectations on the Behavior of Prices - Maccini, Louis J. (American Economic Review, 2016)
The effects of demand and price expectations on price behavior are analyzed, using data from the manufacturing sector and a model formulated to pinpoint the demand-oriented factors affecting prices and to incorporate price expectations as a direct influence on price behavior. The expected normal demand is seen to have a strong and systemic influence on price behavior. The expected normal level of new orders is found to be an adequate measure with sector data in general, although some industries require more specification. The effects of inventories and unfilled orders on prices are sporadic and across sectors and industries. Demand-oriented forces are concluded to perform as well statistically as cost-push determinants. Expectations concerning the current normal industry price level have a significant and consistent impact on price behavior. This supports the idea that firms setting prices take into account their estimates of competitor's prices. Future price expectations appear to have little effect on current price information. 15 references.